Clinical characteristics and treatment outcomes of natural killer/T-cell lymphoma involving the ocular adnexa. Issue 2 (29th April 2018) - Lee, Ga-In; Kim, Yoon-Duck; Young, Stephanie Ming; Shin, Seonae; Woo, Kyung In
Abstract : Aims: To evaluate the clinical characteristics and treatment outcomes of natural killer/T-cell lymphoma (NKTL) involving the ocular adnexa. Methods: Retrospective, comparative, observational case series. A total of 350 patients with NKTL, including 27 patients with NKTL involving the ocular adnexa from 1999 to 2016. The patients were grouped into two groups: group 1 comprised patients presenting with ophthalmic symptoms, and group 2 comprised patients presenting with symptoms from other organs but subsequently developed ophthalmic involvement. Results: Group 1 comprised 12 patients (44.4%) and group 2 comprised 15 (55.6%). Mean duration of symptoms in group 1 was 1.8±1.2 months, while the time from diagnosis of NKTL to development of ophthalmic symptoms in group 2 was 45.3±65.6 months. Periorbital swelling was the most common presenting symptom in both groups (83.3% in group 1 and 73.3% in group 2). Symptoms mimicking cellulitis and pseudotumor were present in 50.0% and 16.7% of cases, respectively. The 5-year overall survival rate was 18.5% in group 1 and 26.4% in group 2, while the 5-year progression-free survival rate was 0% and 13.3%, respectively. Conclusions: Our series is to our knowledge the largest cohort study on NKTL reported to date and demonstrates that ocular adnexal NKTL is a rare but seriously fatal disease. It is characterised by acute inflammatory signs as present in as many as two-thirds of our patients in this series. It should be considered as a differential diagnosis in patients presenting with rapidly progressing proptosis and diagnosed promptly for optimal management.